Influence of anneling condition on the structure and magnetic properties of NdFeB thin films - Luu, Tai Tuan; Than, Hien Duc; Ta, Khoa Van; Le, Tu Tuan (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts